The potential of macroeconomic factors in shaping the landscape of technological development: a testimonial from upper-middle-income countries - Aden Dirir, Sadik (Business, Management and Economics Engineering, 2023)
Purpose – the main goal of the paper is to examine the role of macroeconomic factors in promoting the technological development of upper-middle-income countries.Research methodology – to carry on with the investigation the paper selected the expenditure in research and development as a proxy for technological advancement while GDP per capita, Final consumption expenditure, Domestic credit to the private sector, national income, and government transparency are selected as proxies for the macroeconomic indicators. Moreover, a VECM approach is performed in order to capture the long-run and short-run relationship among the variables. Additionally, a Granger causality test was used to observe the causality direction among the variables.Findings – the obtained results revealed that in the short run, all the selected variables have no prominent impact on R&D expenditure. However, the long run result, presented that the transparency situation of upper-middle-income countries, simultaneously the governments’ final consumption, the amount of credit provided to the private sector, and national income are unfavorably affecting technological development while the GDP is positively affecting the expenditure in R&D.Research limitations – the exclusive focus on macroeconomic factors and upper-middle-income countries as well as the fact of excluding the role of micro factors and low-income countries are the major limitation of the study.Practical implications – policymakers and nations looking to accomplish technological transformation in the age of digitization can benefit from the study’s findings.Originality/Value – since prior studies highlighted the link of macroeconomic factors with specific sectors such as healthcare, education, and agriculture. Thus, giving little attention to or neglecting the information technology sector that compromises a more specific branch such as research and development. For that reason, this paper will bring light to this phenomenon.